(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
The purpose of this descriptive comparative study was to compare the shooting accuracy demonstrated in the matches played at inter collegiate and inter zonal competition held in Pune city in the year 2019-20. A total of 6 matches from inter college tournament and 6 matches from inter zonal tournament played at quarter final, semi-final and final levels were consider to be sample for the study. Shooting accuracy was measured based on the conversion rates of 1 pointer, 2 pointer and 3 pointer field goals. Statistical analysis of the collected data was done based on frequency and percentage of successful conversions. The conversion percentages of the winning team’s 1 pointer successful conversion rate at inter collegiate and zonal level is 36.48 and 48.14 respectively. The 2 pointer successful conversion rate at inter collegiate and zonal level is 50.16 and 53.1 respectively. The 3 pointer successful conversion rate at the inter-collegiate and zonal level is 25.15 and 22.41 respectively. The losing team 1 pointer successful conversion rate by 4.67 at Zonal level competition. The 2 pointer and 3 pointer conversion successful rates decreased by 4.49 and 4.62 respectively at the zonal level. This study concludes that, the inter zonal level shooting accuracy is better than inter collegiate level matches. It was further concluded that the shooting accuracy of winning team is better than losing team.